2000
DOI: 10.1354/vp.37-3-239
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic Detection of Estrogen Receptor Alpha in Canine Mammary Tumors: Clinical and Pathologic Associations and Prognostic Significance

Abstract: Eighty-nine canine mammary tumors and dysplasias of 66 bitches were investigated to determine the immunohistochemical expression of classical estrogen receptor (ER-alpha) and its clinical and pathologic associations and prognostic value. A complete clinical examination was performed and reproductive history was evaluated. After surgery, all animals were followed-up for 18 months, with clinical examinations every 3-4 months. ER-alpha expression was higher in tumors of genitally intact and young bitches (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
167
0
16

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(206 citation statements)
references
References 35 publications
23
167
0
16
Order By: Relevance
“…In the present study, animals with metastasis had lower survival times than did animals without metastasis. These findings are similar to those reported in the literature 22, 23, 24, 25, 26…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, animals with metastasis had lower survival times than did animals without metastasis. These findings are similar to those reported in the literature 22, 23, 24, 25, 26…”
Section: Discussionsupporting
confidence: 93%
“…Corroborating previous findings,22, 23, 24, 25, 26 our study showed that the presence of lymph node metastasis is a negative prognostic factor. However, the analysis of these data with tumor size, histologic type, mitotic index, histologic grading, status of hormonal receptors, and cell proliferation markers may provide more consistent information in a multivariate analysis of the possible independent prognostic factors in dogs with malignant mammary tumors and may provide actual practical applications for the data presented in this study for clinical practice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Studies in other animals have identified similar associations. Increased ER-a and PR expression were found to be correlated with a better prognosis in canine mammary tumours [25,26]. In rabbits with uterine adenocarcinoma, however, expression of ER-a and PR did not reflect prognosis, despite varying hormone receptor expression playing a role in the development of two different types of tumours, papillary or tubular [27].…”
Section: Aetiology Of Urogenital Carcinoma In the California Sea Lionmentioning
confidence: 94%